2003
DOI: 10.1002/kin.10166
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and thermodynamic study of the Na4(UO2)2(OH)4(C2O4)2 complex

Abstract: The synthesis, the characterization, and the thermal decomposition of the dioxouranium(VI) ternary complex of formula Na 4 (UO 2 ) 2 (OH) 4 (C 2 O 4 ) 2 , has been studied. The identification of the compound was performed by chemical analysis and infrared spectrometry. Thermal decomposition of the compound occurs in several steps due to the decomposition of the salt to Na 2 O and UO 3 oxides. The stoichiometry of the steps, hypothesized by means of the thermodynamic and kinetic parameters, is confirmed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Two hydroxooxalato uranates have been reported, Na 4 [(UO 2 ) 2 (C 2 O 4 ) 2 (OH) 4 ] [38,39] with an unknown structure and NH 4 [(UO 2 ) 2 (C 2 O 4 ) 2 (OH)] Á 8H 2 O [37]. In this last compound the structure is built from an other SPBU formed by two OH corner-shared UO 7 pentagonal bipyramids which contain in the equatorial base four oxygen from two oxalate entities that connect the SPBU in a 2D network.…”
Section: Article In Pressmentioning
confidence: 99%
“…Two hydroxooxalato uranates have been reported, Na 4 [(UO 2 ) 2 (C 2 O 4 ) 2 (OH) 4 ] [38,39] with an unknown structure and NH 4 [(UO 2 ) 2 (C 2 O 4 ) 2 (OH)] Á 8H 2 O [37]. In this last compound the structure is built from an other SPBU formed by two OH corner-shared UO 7 pentagonal bipyramids which contain in the equatorial base four oxygen from two oxalate entities that connect the SPBU in a 2D network.…”
Section: Article In Pressmentioning
confidence: 99%
“…As Folnak ® constitutes complexly, its degradation reaction is actually parallel, concurrent, or consecutive reaction processes of many elementary reactions (35). In addition, thermogravimetric analysis measures the relationship between the overall quality and temperature, and α denoted that the extent of reaction is just an apparent and integrated concept, which showed that it is impossible that this change of the quality reasonably attributed some one elementary.…”
Section: The Evaluation Of the Kinetic Model Functionmentioning
confidence: 99%